(untitled) (Research, Society and Development, 2026)
This article aims to describe, through a case study, the application of the cerclage technique in a Holstein calf with a mandibular fracture, highlighting the clinical and surgical aspects applied, as well as the postoperative evolution. In cattle, food is primarily captured using the tongue, while smaller particles are captured by the lips. Any alteration in the anatomical components involved in the prehension and chewing process results in decreased appetite and weight gain. Mandibular fractures in calves, associated with bone immaturity and trauma, compromise masticatory function, requiring veterinary intervention. The calf was six months old and presented with dysphagia, sialorrhea, and dental misalignment, with the diagnosis confirmed by clinical and imaging examination, revealing a 10 cm longitudinal mandibular fracture. Osteosynthesis was performed with stainless steel wire cerclage (0.8 mm) and application of acrylic resin, ensuring adequate stabilization. Post-operative care included antibiotic therapy, anti-inflammatories, and daily cleaning, resulting in uncomplicated bone consolidation and clinical discharge in 50 days. It is concluded that the technique is effective and low-cost for mandibular fractures in calves.